Influence of Installation Conditions on Heating Bodies Thermal Output: Preliminary Experimental Results. (November 2016) - Arpino, F.; Cortellessa, G.; Dell'Isola, M.; Ficco, G.; Marchesi, R.; Tarini, C.
Abstract: Heating bodies are thermodynamic systems whose heat output is strongly dependent on boundary conditions and in about a century several attempts have been made for its experimental determination. To this aim, at the beginning of 60s, in Europe different national standards were adopted (e.g. in 1967 in Italy the UNI 6514/1967). At European level, the EN 442-1:2014 and EN 442-2:2014 allows the heating body heat output estimation with an expanded uncertainty lower than 1% and they are now accepted in various international markets. The EN 442 also allows heat output calculation in operating conditions different from standard ones by employing theoretical-experimental correlations that, by their nature, are not able to include any possible actual operating condition. In fact, in actual operating conditions the heating body heat output depends on several factors, among which: i) installation position with respect to the wall and the floor; ii) presence grid/shelf/niche or an obstruction caused by curtains on the heating body; iii) thermo-fluid-dynamic condition variations (inlet flow rate and temperature); iv) hydraulic connections. Radiators represent the most spread heating body (installed since the end of '800) and in the last decades different radiators typologies have been proposed on the market, characterized by different materials, sizes, shapes, etc. In the present paper the authors present the preliminary result of an experimental campaign on field for the heat output measurement of different radiators typologies (cast iron, aluminum) as a function of different installation and operating conditions. The influence on the heating body performance and the associate technical-economical consequences in terms of heat cost allocation accuracy have been investigated.